Peran Pembimbing Kemasyarakatan dalam Penanganan Anak yang Berhadapan dengan Hukum - Riyadi Riyadi (Jurnal Syntax Admiration, 2023)
Children involved in legal problems (ABH) need proper assistance and guidance in order to get protection, rehabilitation, and opportunities to improve their behavior and future. The purpose of this study is to explore and understand the role of community supervisors in handling children in conflict with the law. This research uses qualitative research methods. The data collection technique was carried out by literature study. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results showed that community supervisors have an important role in handling ABH. The role of community supervisors includes helping ABH to understand their rights and obligations as ABH, helping ABH to undergo the legal process properly, helping ABH to return to society properly, and helping ABH to become good citizens.